2022
DOI: 10.31098/tsdr.v3i2.66
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Tourism in Pandemic: Community Health and Welfare Solutions

Abstract: Outdoor tourism is becoming a trend and is increasingly in demand during the pandemic. This tourism is considered the safest and most comfortable choice after two years of the community being limited in all their activities. This article aims to observe what forms of outdoor tourism are and how these tours are a solution to maintaining health and supporting community welfare. Through a qualitative approach with a case study method, it can be found forms and ways in which outdoor tourism in Sentul, Bogor can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Result of this study shows Tegal Waru Tourism Village offers great cultural potential and the involvement of community participation is the key to successful tourism. Dewi et al, (2022) observed forms of outdoor tourism and the preservation of the natural environment and culture of its people.…”
Section: Finding and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Result of this study shows Tegal Waru Tourism Village offers great cultural potential and the involvement of community participation is the key to successful tourism. Dewi et al, (2022) observed forms of outdoor tourism and the preservation of the natural environment and culture of its people.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…This section reviews the literature related to tourism in specific context. Studies have been conducted by Handoyo et al (2017), Latianingsih (2020), Fitri dan Siska (2021), Rejeki andSwetasurya (2023), andDewi et al, (2022). Handoyo et al (2017) researched how far travel agents in special Region of Yogyakarta can create tour package for people with disabilities.…”
Section: Previous Related Researchmentioning
confidence: 99%
See 1 more Smart Citation